Impact of catheter-directed thrombolysis access approach on entire-limb deep vein thrombosis: a focus on inflow patency - Qian, Cheng; Jiang, Wei-Qing; Guo, Kang; Wang, Tao; Lou, Wen-Sheng; Li, Ying-Hao; Gu, Jian-Ping; Chen, Guo-Ping (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThis retrospective study aimed to evaluate the influence of inflow (femoropopliteal) patency on the efficacy of catheter-directed thrombolysis (CDT) in treating entire-limb deep venous thrombosis (DVT).MethodsFrom January 2018 to December 2022, 121 individuals diagnosed with acute entire-limb DVT were treated with CDT. CDT was performed through the ipsilateral popliteal vein (AGA) or the contralateral common femoral vein (RGA). Baseline characteristics and segmental patency were compared between the two access approaches groups. The severity of post-thrombotic syndrome (PTS) was compared between different inflow patency groups. Propensity-score matching (PSM) was used to balance confounding factors. Potential risk factors for PTS were analyzed using univariate and multivariate regression analysis.ResultsThirty-four patients received the AGA approach, while 87 individuals were treated with the RGA approach. The AGA group had superior patency compared to the RGA group in both the popliteal and femoral veins (P < 0.0001). “Good” inflow (great and fair patency) was associated with a lower PTS incidence and severity compared to “bad” inflow (poor patency) (P < 0.0001). Most patients with “bad” inflow (94.1%) received the retrograde approach. The PSM analysis yielded 97 well-matched pairs (59 patients in the “good” inflow group, and 38 in the “bad” inflow group). The access approach did not significantly affect PTS rate. Multivariate analysis identified “bad” inflow patency as a predictor of PTS (OR: 3.41, 95% CI: 1.94–6, P < 0.0001), further treatment showed a protective effect (OR: 0.17, 95% CI: 0.1–0.3, P < 0.0001).Conclusion“Good” inflow patency decreased the incidence and degree of PTS among patients with entire-limb DVT.